Opportunistic mycobacterial diseases. (June 2020) - Meghji, Jamilah; Kon, Onn Min
Abstract: Non-tuberculous mycobacteria (NTM) are hardy environmental organisms: >200 species have been identified, with highly variable pathogenicity. NTM infection is usually acquired from the environment and can be asymptomatic or associated with pulmonary disease (NTM-PD), particularly in patients with immunocompromise, chronic lung conditions or impaired mucociliary clearance. The incidence of NTM isolates and NTM-PD is rising in resource-rich settings. Diagnosis of NTM-PD requires both positive microbiology and typical clinical and radiological features. Treatment typically requires multidrug therapy for at least 12 months, with a combination of oral, nebulized and intravenous antibiotics depending on the NTM species, severity of disease, drug resistance patterns and treatment response. Surgery can be used for localized refractory disease. Outcomes are highly variable and cure may not be possible. Disease should be managed in specialized multidisciplinary team settings where possible.